A qualitative study of client and healthcare provider perspectives on the role of stigma in self-directed discharge for people who inject drugs with injecting-related infections - Liam S. Acheson; Loren Brener; Krista J. Siefried; Maureen Steele; Cilla Zhou; Gail V. Matthews; Nadine Ezard; Brendan Clifford (BMC Health Services Research, 2026)
Abstract Background People who inject drugs admitted to hospital can experience stigma, increasing the risk of self-directed discharge (SDD), incomplete treatment and potential subsequent avoidable harms. This study aimed to explore the perspectives of patients and clinicians in an urban Australian hospital setting for higher rates of SDD amongst people who inject drugs. Methods A qualitative study design using semi-structured interviews. One-on-one interviews were conducted with (1) patients who inject drugs and (2) clinicians who routinely care for people who inject drugs at a major tertiary hospital in Sydney, Australia. Patient participants were recruited through a review of admission records and referral from clinicians and clinician participants through consultation with relevant service managers. Interview transcripts were analysed using thematic analysis to explore experiences around stigma and the relationship to SDD. Results Five patients and eight clinicians participated in qualitative semi-structured interviews. Thematic produced three themes related to interpersonal stigma (perceptions of drug seeking, pain management, care experiences) and three themes related to structural stigma (double standards, hospital culture, access constrained by stigma). Whereas patients mainly attributed SDD to unmet medical and psychosocial needs due to stigma, clinicians primarily felt that the desire to use drugs and external social factors drove SDD. Conclusions This study supports the need for further stigma reduction education for clinicians and action at an institutional level on drug-related stigma. This may improve patient experiences and potentially reduce rates of SDD.